Enhancing the mechanical properties of electron beam welded TC17 titanium alloy joint by post-weld heat treatment - Liu, Hanqing; Wang, Haomin; Zhang, Zhen; Huang, Zhiyong; Liu, Yongjie; Wang, Qingyuan; Chen, Qiang (Journal of alloys and compounds, 2019)
Supersaturated coarsening β phase and submicron acicular martensitic α′ phase originated by the high cooling rate during the welding process resulted in the electron beam welded TC17 titanium weldment to be poor in strength and ductility. Post-weld heat treatment was performed at 630 °C for 2 h to improve the mechanical properties of electron beam welded TC17 titanium alloy joint through modifying the microstructures of the weldment. Results showed that undesired α′ martensites in the fusion zone and heat affected zone, which inhibited the mechanical response of the weldment, were completely eliminated. The supersaturated β phase with martensitic α′ structure in the as-welded joint was recrystallized into α lamella with a width in nanoscale embedded in the β matrix after the post-weld heat treatment, which conspicuously enhanced the mechanical performances of welded joints. Micro-hardness of the FZ presented to be more stable around HV410. Tensile strength was regained from 868 MPa to 1138 MPa, which was very closed to the raw material. Intrinsic metallic deficiency inducing fatigue failure of the as-welded joint was eliminated after the post-weld heat treatment accompanied with the fatigue strength enhancing from about 140 MPa of the as-welded joint to 240 MPa with an equal fatigue life of 107 cycles under the stress ratio of 0.1. [Display omitted] •Post-weld heat treatment was performed on the electron beam welded TC17 titanium alloy joint.•Martensitic α′ phase was sufficiently disintegrated and recrystallized into β phase with nano α lamellas.•The joint showed great micro-hardness stability after post-weld heat treatment.•Tensile and fatigue strength was significantly enhanced.